Soborowe źródła prawa małżeńskiego w Kodeksie prawa kanonicznego z 1983 roku - Saj, Marek (Ius Matrimoniale, 2020)
Documents of the Second Vatican Council became essential root of the Canon Code Law of 1983. There is a number of references to conciliar constitutions, decrees and declarations in each Canon Book. This is true also in regard to the marital law included in Ćanons 1055-1165. Amongst sources which were inspirations for the aforementioned marital law there were the following constitutions: Sacrosanctum Concilium, Lumen gentium, and Gaudium et spes; and decrees: Orientalium...., Unitatis..., Christus...and Apostolicum and also Gravissimum. Lawmaker makes 34 references to these documents. The conducted analysis allows to show to what extend norms of the marital law remain under the influence of the Second Vatican Council.